Evaluation of improved cassava genotypes for fresh root yield and yield components in demand creation trial - Onyenali, T.C.; Ogwuche, T.O.; Onyeka, J.; Diebiru-Ojo, E.M.; Ikechukwu, I.; Abah, S.P.; Okwuonu, I.C.; Ameh, E.A.; Sanni, L.; Kulakow, P.; Egesi, C. (Frontiers Media, 2025)
Fresh yield and dry matter concentration are important traits that promote the adoption of improved cassava varieties by processors and their out-grower farmers in southeastern Nigeria. Therefore, for wide adoption of improved cassava varieties developed by the International Institute of Tropical Agriculture, Ibadan, and National Root Crops Research Institute, Umudike, there is a need to evaluate improved varieties for these attributes continuously, hence the need to explore variety decision support tool like the demand creation trials (DCT) to evaluate cassava varieties with farmers and processors utilizing the best agronomic practices. The DCTs were conducted in three environments during the 2020–2021 and 2021–2022 cropping seasons with two replications. A randomised complete block design (RCBD) was used for this study with four improved varieties. The plot size was 320 m2 with a 1 m x 0.8 m spacing. The traits evaluated were Plant Vigor (PV), number of storage roots, fresh yield, dry yield, Dry Matter Content (DMC), and bundle estimation. The traits were subjected to a GGE biplot in R software to identify high-yielding and stable genotypes. The estimated marginal means (EMM) for cassava yieldwere compared across different clones, environments, and years, revealing significant differences (p < 0.01). According to the result, Variety TMS13F1160P0004 had the highest fresh root yields of 37.61 t/ha and 35.46 t/ha in 2021 at the Abia and Owerri locations, respectively. Additionally, variety TMS13F1160P0004 had the best dry yield in 2021, with 12.81 t/ha in Abia and 11.73 t/ha in Owerri. According to the genotype by environment interaction analysis, yield estimates varied greatly, especially for CR36-5 and IBA980693, although varieties TMS13F1160P0004 and IBA961632 were more stable across environments. For dry matter content (%), there was no discernible difference across the varieties. These findings showed the significance of conducting DCTs across various environmentss with independent cassava processors to to guide their choices of cassava varieties for factory operations.